18F-FDG PET/TC na avaliação de resposta terapêutica à quimio-radioterapia neoadjuvante em pacientes com câncer de reto - Theara Cendi Fagundes (2014)
Rectal cancer is a neoplasm disease of global importance and Brazilian estimates for 2014, 32,600 new cases of colorectal cancer, of these 15,070 in men and 17,530 in women. Nowadays the standard treatment for locally advanced mid and low rectal cancer comprises combined modality with chemotherapy and radiotherapy and radical surgery after six to eight weeks. The ability to predict responders from non-responders to preoperative chemoradiation in rectal cancer by conventional imaging (CT, ultrasound, MR) alone or in combination is a difficult task before the histopathological analysis of the surgical specimen. The use of 18F-FDG PET/CT has been proposed in studies worldwide for the purpose of assessing response noninvasively through anatomical and molecular analysis. This study aimed to analyze the incorporation of this new technology 18F-FDG PET / CT and its impact on response evaluation of patients with rectal cancer undergoing neoadjuvant chemoradiation in the Brazilian reality. The sample consisted of patients with stage II and III rectal cancer that underwent 18F-FDG PET/CT examination at UFMG Center for Technology in Molecular Medicine from March 2012 to November 2013 whom were referred from Colorectal and Oncology ambulatory from Hospital das Clínicas. Among 23 patients, after identifying the inclusion criteria, 17 patients were analyzed. Significant differences were observed between responders (Dworak 3 and 4) and non-responders for SUVmed2 (p = 0.012) and SUVmax2 (p = 0.009). Considering only patients with pathologic complete response and applying ROC analysis, the following variables showed significant results: % SUVmed with AUC = 0.896, CI was found: 0642-0991, p = 0.0001, with the benchmark in 68.8 with 83.3% sensitivity and 100% specificity; %SUVmax response with AUC = 0.923, CI: 0688-0996, p = 0.0001, with the benchmark in 68.8 with 84.6% sensitivity and 100% specificity; %TLG with AUC = 0.788, CI: 0527-0945, p = 0:03, with reference point at 85.1% with 61.5% sensitivity and 100% specificity. Regardless the reability of these results, we still cant restrict offering radical surgery to patients with response to 18F-FDG PET/CT images.